Unraveling the Transformation of Public Administration: Business Curriculum Innovation as a Solution in Organizational Dynamics - Arthur Kadakure; Michael Twum-Darko (Managere: Indonesian Journal of Educational Management, 2025)
This study focuses on the dynamics of structural changes in public administration and their implications for developing the business education curriculum at Cape Peninsula University. In the era of globalization and rapid technological advancement, public administration must adapt to the demands of an increasingly complex external and internal environment. The research method used is a qualitative approach with a case study design involving ten resource persons from various departments at the university. Data was collected through in-depth interviews, participatory observations, and analysis of public policy documentation. The study results show a paradigm shift from the traditional hierarchical structure to a more flexible and responsive organizational model, which is characterized by the implementation of cross-functional teams and increased collaboration between departments. In addition, adopting New Public Administration (NPA) principles in public policy strengthens the efficiency and accountability of public services despite facing challenges such as internal resistance and resource limitations. The implication of these findings is the need to integrate elements of public administration into the business education curriculum to equip students with adaptive and innovative managerial skills. This is expected to increase the practical relevance of the curriculum to the needs of the ever-evolving industry and prepare graduates who are ready to face the dynamics of the complex world of work.